Addition of lemuru fish oil in the diet on the fat retention and fatty acid profile of silver barb (Rasbora argyrotaenia). Issue 1 (February 2020) - Marini, A; Mubarak, A S; Mukti, A T
Abstract: One important factor in cultivation is feed. The addition of fish oil to feed affects the activity of the protein and cell synthesis so that it affects the growth rate, feed conversion ratio, and protein and fat contents of the fish body. This study aimed to determine the effect of the addition of lemuru fish oil in feed on fat retention and fatty acid profiles of silver barb ( Rasbora argyrotaenia ) fish. This study was used as an experimental method with a completely randomized design consisting of five treatments and four replications for each treatment. The lemuru fish oil with different concentrations, namely 0, 2, 4, 6, and 8% were added to commercial feed of silver barb. The parameters of fat retention and fatty acid profile were observed. Data were analyzed statistically using a variant of analysis followed by Duncan's multiple range test. The results showed that the addition of lemuru fish oil in the fish feed for 40 days of fish rearing had a significant effect (p<0.05) on fat retention and increased fatty acid profile of silver barb. The 2% treatment has the best of fat retention (53.36%). A fat concentration of 9% in the diet increase unsaturated fatty acids content of silver barb (66.32%).